Image-Quality Assessment of 3D Intracranial Vessel Wall MRI Using DANTE or DANTE-CAIPI for Blood Suppression and Imaging Acceleration - Sannananja, B.; Zhu, C.; Colip, C.G.; Somasundaram, A.; Ibrahim, M.; Khrisat, T.; Mossa-Basha, M. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: 3D intracranial vessel wall MRI techniques are time consuming and prone to artifacts, especially flow artifacts. Our aim was to compare the image quality of accelerated and flow-suppressed 3D intracranial vessel wall MR imaging techniques relative to conventional acquisitions.MATERIALS AND METHODS: Consecutive patients undergoing MR imaging had conventional postcontrast 3D T1-sampling perfection with application-optimized contrasts by using different flip angle evolution (SPACE) and either postcontrast delay alternating with nutation for tailored excitation (DANTE) flow-suppressed or DANTE–controlled aliasing in parallel imaging results in higher acceleration (CAIPI) flow-suppressed and accelerated T1-SPACE sequences performed. The sequences were evaluated using 4- or 5-point Likert scales for overall image quality, SNR, extent/severity of artifacts, motion, blood suppression, sharpness, and lesion assessment. Quantitative assessment of lumen and wall-to-lumen contrast ratios was performed.RESULTS: Eighty-nine patients were included. T1-DANTE-SPACE had significantly better qualitative ratings relative to T1-SPACE for image quality, SNR, artifact impact, arterial and venous suppression, and lesion assessment (P < .001 for each, respectively), with the exception of motion (P = .16). T1-DANTE-CAIPI-SPACE had significantly better image quality, lesion assessment, arterial and venous blood suppression, less artifact impact, and less motion compared with T1-SPACE (P < .001 for each, respectively). The SNR was higher with T1-SPACE compared with T1-DANTE-CAIPI-SPACE (P < .001). T1-DANTE-CAIPI-SPACE showed significantly worse lumen (P = .005) and wall-to-lumen contrast ratios (P = .001) compared with T1-SPACE, without a significant difference between T1-SPACE and T1-DANTE-SPACE. T1-DANTE-CAIPI-SPACE scan time was 5:11 minutes compared with 8:08 and 8:41 minutes for conventional T1-SPACE and T1-DANTE-SPACE, respectively.CONCLUSIONS: Accelerated postcontrast T1-DANTE-CAIPI-SPACE had fewer image artifacts, less motion, improved blood suppression, and a shorter scan time, but lower qualitative and quantitative SNR ratings relative to conventional T1-SPACE intracranial vessel wall MR imaging. Postcontrast T1-DANTE-SPACE had superior SNR, blood suppression, higher image quality, and fewer image artifacts, but slightly longer scan times relative to T1-SPACE.CAIPIcontrolled aliasing in parallel imaging results in higher accelerationDANTEdelay alternating with nutation for tailored excitationIVWintracranial vessel wall MR imagingMSDEmotion-sensitized driven-equilibriumSPACEsampling perfection with application-optimized contrasts by using different flip angle evolution